2013
DOI: 10.5888/pcd10.120288
|View full text |Cite
|
Sign up to set email alerts
|

Survey of New York City Resident Physicians on Cause-of-Death Reporting, 2010

Abstract: IntroductionDeath certificates contain critical information for epidemiology, public health research, disease surveillance, and community health programs. In most teaching hospitals, resident physicians complete death certificates. The objective of this study was to examine the experiences and opinions of physician residents in New York City on the accuracy of the cause-of-death reporting system.MethodsIn May and June 2010, we conducted an anonymous, Internet-based, 32-question survey of all internal medicine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 10 publications
0
49
1
Order By: Relevance
“…For example, the New York City medical examiner's policy of rejecting New York City death certificates with sepsis listed alone as the single underlying cause of death (without other contributing causes) has been misinterpreted by some clinicians to mean that the term "sepsis" was not permitted to be included anywhere on the death certificate, thus affecting estimates of sepsis-related mortality (8). In addition, it is important to note that death certificates are often completed by physicians with varying levels of training in completing death certificates; data from a survey of resident physicians in New York City showed that only 40% reported receiving any training by their residency program regarding completion of death certificates (9). Finally, sepsis can be confused with other acute medical problems, such as myocardial infarction, that frequently cause mortality in the community setting.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the New York City medical examiner's policy of rejecting New York City death certificates with sepsis listed alone as the single underlying cause of death (without other contributing causes) has been misinterpreted by some clinicians to mean that the term "sepsis" was not permitted to be included anywhere on the death certificate, thus affecting estimates of sepsis-related mortality (8). In addition, it is important to note that death certificates are often completed by physicians with varying levels of training in completing death certificates; data from a survey of resident physicians in New York City showed that only 40% reported receiving any training by their residency program regarding completion of death certificates (9). Finally, sepsis can be confused with other acute medical problems, such as myocardial infarction, that frequently cause mortality in the community setting.…”
Section: Discussionmentioning
confidence: 99%
“…Causes of death recorded on death certificates are notoriously inaccurate and do not have a standard format [12,13]. In one large study by Mayr et al [14], the reason for death was determined in 3700 critically ill patients, a minority of whom had been admitted with sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…We did not examine cause of death as this is subject to significant misclassification in administrative databases (40, 41). We did not find any differences in infections or narcotic use that would explain the difference in mortality rates.…”
Section: Discussionmentioning
confidence: 99%